1984
DOI: 10.1029/gl011i009p00899
|View full text |Cite
|
Sign up to set email alerts
|

Radar and satellite measurements of an F‐region ionization enhancement in the post‐noon sector

Abstract: A post‐noon enhancement in F‐region ionization has been studied using data from the Sondrestrom radar and the NOAA‐7 and Triad satellites. This enhancement is seen quite often in Sondrestrom radar data. It is extended in the east‐west direction and is the site of elevated electron temperatures. Data from the Triad satellite indicate that the enhancement observed on 9 September 1983 was collocated with intense upward field‐aligned currents. The NOAA‐7 satellite measured an electron spectrum in association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Based on the observations with ISIS 2 scanning photometer, Cogger et al [1] first noticed that dayside aurora had an enhancement in [14][15][16] MLT sector where happens to be the peak position of the upward region 1 field-aligned current [2] . Incoherent scattering radar observations showed that F layer electron density was frequently enhanced in this sector [3] , and the postnoon auroral "hot spot" also occurs there [4] . It is a hot topic to study the dependence of the postnoon aurora upon the interplanetary magnetic field (IMF) and the solar wind parameters.…”
Section: Introductionmentioning
confidence: 93%
“…Based on the observations with ISIS 2 scanning photometer, Cogger et al [1] first noticed that dayside aurora had an enhancement in [14][15][16] MLT sector where happens to be the peak position of the upward region 1 field-aligned current [2] . Incoherent scattering radar observations showed that F layer electron density was frequently enhanced in this sector [3] , and the postnoon auroral "hot spot" also occurs there [4] . It is a hot topic to study the dependence of the postnoon aurora upon the interplanetary magnetic field (IMF) and the solar wind parameters.…”
Section: Introductionmentioning
confidence: 93%
“…It is this ionisation that results in the E-and F-region features, imaged by the tomographic technique, that are coincident with the auroral features observed by ground-based optical instrumentation. Robinson et al (1984), using the Sondre Stromfjord incoherent scatter radar, studied an F-region ionisation enhancement with a peak height of around 250 km associated with an upward ®eld-aligned current populated by 350 eV electrons. The density of the enhancement was around 2´10 11 m…”
Section: Discussionmentioning
confidence: 99%
“…Evans (1985) found from satellite data analysis that precipitating electrons in the energy range 0.3±3 keV carried the current out of the ionosphere in latitudinally thin structures ($20 km average width) in this local time sector. Robinson et al (1984) presented incoherent scatter measurements of an ionospheric Fregion density enhancement attributed to an upward ®eld-aligned current. They concluded that the associated electron beam located at the electric ®eld reversal, produced a region of enhanced electron density by a process similar to that established for evening sector auroral arcs, but with less energetic electrons.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reported ground-based and satellite investigations of the thermospheric and ionospheric responses to the soft electron precipitation and ®eld-aligned current variations in the cusp region (e.g., Shepherd, 1979;Kelly and Vickrey, 1984;Kofman and Wickwar, 1984;McCormac and Smith, 1984;Oliver et al, 1984;Robinson et al, 1984;Smith, 1984;Vennerstrom et al, 1984;Wickwar, 1984;Thayer et al, 1987;Sandholt et al, 1994;Wu et al, 1996). However, there have been no reported systematic observational pictures of the seasonal behaviour of the thermospheric and ionospheric disturbances in the cusp region, partly due to the suppressive in¯uence of the solar emission on the ionization and heating processes in the summer polar upper atmosphere.…”
Section: Introductionmentioning
confidence: 99%